2013
DOI: 10.2147/jmdh.s39158
|View full text |Cite
|
Sign up to set email alerts
|

Effect of TNF antagonists on the productivity of daily work of patients with rheumatoid arthritis

Abstract: Rheumatoid arthritis (RA) is a significant cause of work disability and job loss. The resulting economic burden experienced by patients has received considerable research attention. This research assesses the effect of tumor necrosis factor (TNF) antagonists (infliximab, etanercept) on the ability of RA patients living in Japan to work and participate in society. A total of 42 patients with active RA were enrolled and given biological therapy for 12 months (mo). Of these patients, 14 were employed full-time, 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Significant decreases in DAS28CRP obtained in this real-world setting were consistent with those reported in clinical trials of 24- to 52-week duration, as well as a 24-week post-marketing surveillance study conducted in Japan [ 27 , 39 , 47 , 48 ]. Importantly, in the present large-scale study, improvements in WPAI/RA showed a weak to moderately strong positive linear correlation with improvement in disease activity, extending the findings from a previous small-scale study assessing the effects of TNF-α antagonists on DAS28ESR and work productivity in 42 patients [ 15 ].…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Significant decreases in DAS28CRP obtained in this real-world setting were consistent with those reported in clinical trials of 24- to 52-week duration, as well as a 24-week post-marketing surveillance study conducted in Japan [ 27 , 39 , 47 , 48 ]. Importantly, in the present large-scale study, improvements in WPAI/RA showed a weak to moderately strong positive linear correlation with improvement in disease activity, extending the findings from a previous small-scale study assessing the effects of TNF-α antagonists on DAS28ESR and work productivity in 42 patients [ 15 ].…”
Section: Discussionsupporting
confidence: 85%
“…These results are within the range presented in a systematic literature review evaluating randomized controlled trials showing the effect of biologics on the reduction in days of sick leave (ranging from 2.1 days in 4 weeks to 18.7 days in 2 years) [ 49 ]. A favorable effect of biologics on daily work-related productivity has been reported in Japan [ 15 ]. Concomitant use of MTX was also a factor associated with presenteeism, OWI, and AI, and shorter disease duration was another factor associated with AI for HMs in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations